Intravenous immunoglobulin: Revisited - My experience - Sanjeev S Vaishampayan; Surendra Singh Bhati; Radha R Lachhiramani; Shivank Shrivastava; Prateek Jain; Ajay Singh Raghuwanshi (Wolters Kluwer Medknow Publications, 2021)
Background: Many a times while treating dermatoses conventional therapies are either contraindicated or not effective. Intravenous immunoglobulin (IVIG) is a good alternative available to tide over crises. Method: Over the last 15 years of my practice I have used IVIg in various severe or recalcitrant diseases (including TEN, autoimmune blistering disease,connective tissue disorders , chronic urticaria etc) which were either unresponsive to conventional modality of therapy or primary therapy could not be given because of co-morbidities. Result: IVIg a sterile, highly purified preparation containing more than 95% unmodified IgG,was first approved by FDA in 1981 for 6 diseases. As mentioned above in many circumstances we reached a situation when either conventional primary therapy was contraindicated or patients were not responding. IVIg came to our rescue in large number of conditions to tide over the crisis and also created the environment leading to conventional therapy becoming effective. Very few minor side effects like low grade fever and myalgia were observed in very few cases. No serious or severe side effects were seen, however , one has to be prepared for anaphylactic reaction which is a theoretical possibility. Conclusion: It can be said that IVIg though not a magic drug, is a very effective tool available in the armamentarium of Dermatologists to treat plethora of chronic and intractable dermatoses.